If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -7 = 43 Reorder the terms: -7 + 18x = 43 Solving -7 + 18x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 18x = 43 + 7 Combine like terms: -7 + 7 = 0 0 + 18x = 43 + 7 18x = 43 + 7 Combine like terms: 43 + 7 = 50 18x = 50 Divide each side by '18'. x = 2.777777778 Simplifying x = 2.777777778
| 4a^2+28ap+49p^2= | | 2=27 | | 5x-3=6-2x | | 25b^2-60b+36= | | -11m+(-6m)= | | -16m-(-38m)+12m= | | 1/5(3-6x)=1/30+x/2 | | 14+6y=8(y-1) | | -15=+(-5) | | 9-5x=3/4+12x | | 32k=896 | | -3x=.5 | | l^2-5l+6=0 | | 19+k=32 | | y/3=-19 | | 0.30x+0.05(20-x)=0.10(25) | | 8(h+2)-5(h-1)=6h | | 2x^2+40x+180=0 | | 5y+2y(y-6)=4(y+1)-2 | | X+3/4x=84 | | 10x-41=69 | | 9t-16r=-49 | | 2x^3-40x+192xy^2=0 | | x^2-2*435*x+(2*11.637*(10^6))/(0.9*0.85*20.7*800)=0 | | x^2-2*435*x+2*11.637*10^6/0.9*0.85*20.7*800=0 | | x^2-2*435*x+2*11.637/0.9*0.85*20.7*800=0 | | -4*5-4y=16 | | -3(2x+1)=x+9 | | 9*3+9y=81 | | 2(k+2)+6(k-2)=5k-2 | | .5t+15=-10 | | (7x-3)(12x-7)= |